Repair of giant inguino-scrotal hernia with loss of domain using minimally invasive anterior component separation technique combined with Lichtenstein tension-free mesh hernioplasty - Sewalia, Pooja; Chawla, Avneet S.; Sangtam, Lirangla T.; Mandalapu, Himaja; Kumar, Hemant; Kaur, Avneet; Bansal, Anshul (International Surgery Journal, 2020)
Inguinal hernia repairs are most commonly performed surgical procedures across the world. Lichtenstein’s tension free technique of open hernioplasty is the gold standard technique, while laparoscopic techniques gained popularity over recent decade. Giant inguinal hernias are rare. Giant inguinal hernia extends below the midpoint of the inner thigh, in the standing position. These are long standing conditions and at presentation years of herniation or even decades. We report a patient of 65 years of age presented with type-II left sided giant inguinoscrotal hernia from last 10 years with loss of domain. Contrast enhanced computed tomography (CECT) revealed, omentum and ileal loops with mesentry as contained in hernia sac, which was repaired by minimally invasive anterior component separation technique to increase the intra-abdominal volume followed by omentectomy and Lichtenstein mesh hernioplasty without any complications. He recovered uneventfully. Surgical management of giant inguinal hernia is significantly more challenging and unusual because of ‘loss of domain’ and returning herniated viscera into the empty abdominal cavity forcefully can lead to high intra-abdominal pressure, recurrence or abdominal compartment syndrome. There are several repair techniques in literatures such as resection of contents and increased intra-abdominal volume increasing procedures but there is no standard protocol or surgical procedure for the management of giant hernias. We describe a technique which is relatively simple, less expensive and less invasive used for type II unilateral giant inguinoscrotal hernia with loss of domain in patient with co-morbidities.